Kajian Teologi Misi dalam Roma 10:13-15 terhadap Aktualisasi Misi Kristen - Arifianto, Yonatan Alex (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2021)
Abstract: Evangelism as a means of bringing people together with God through testimony or example must continue to be echoed. However, there are many different paradigms and concepts of evangelism. Moreover, churches and believers are reluctant to do evangelism because they do not consider it their duty and responsibility. Indeed, believers do not escape the actualization of the mandate of the Great Commission of the Lord Jesus in preaching the gospel to humans. Using a descriptive qualitative method with a literature study approach, it can be concluded that the study of mission theology in Romans 10:13-15 on the actualization of Christian missions studied through exegesis can be concluded, First, evangelism must be carried out as part of the actualization of the mandate of the Great Commission by giving oneself to preach the news to others so that People who don't know Jesus can hear salvation only in Jesus. Second, the task of the believer is continued as a person who continues to preach by listening and proclaiming the gospel of salvation for humans. The three churches or leaders are obliged to send messengers of evangelists for the sake of saving souls. Abstrak:Penginjilan sebagai sarana mempertemukan manusia dengan Tuhan lewat kesaksian ataupun keteladannan harus terus digaungkan. Namun banyaknya perbedaan paradigma dan konsep pengijilan. Terlebih gereja maupun orang percaya enggan melakukan penginjilan karena bukan mengangap bahwa tugas dan tanggung jawabnya. Sejatinya orang percaya tidak luput dari aktualisasi mandat Amanat Agung Tuhan Yesus dalam melakukan pemberitaan Injil kepada manusia. Mengunakan meotode kualitatif deskritif dengan pendekatan studi literature bahwa kajian Teologi misi dalam Roma 10:13-15 terhadap aktualisasi misi Kristen yang dikaji melalui eksegesa dapat disimpulkan, Pertama Penginjilan harus terus dilakukan sebabgai bagian aktualisasi mandat Amanat Agung dengan memberi diri untuk memberitakan kabar bagi sesama sehingga orang yang belum mengenal Yesus dapat mendengar keslematan hanya didalam Yesus. Kedua, Tugas orang percaya dilanjutkan sebagai pribadi yang terus menerus melakukan pemberitaan dengan Memperdengarkan dan memberitakan Injil keselamatan bagi manusia. Ketiga Gereja atau pemimpin wajib mengirimkan utusan Pemberita Injil demi jiwa jiwa diselamatkan.